2018
DOI: 10.30651/jkm.v2i2.1026
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Derajat Neuropati Dengan Keseimbangan Fungsional Pada Pasien Neuropati Diabetik

Abstract: Chronic hyperglycemia in Diabetes Mellitus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The results showed that the incidence of peripheral neuropathy was more experienced by women (Table 3). By some previous studies, it is stated that about 53% more who experience peripheral neuropathy are women (30,31).…”
Section: Overview Of Peripheral Neuropathy Based On Demographic Characteristicsmentioning
confidence: 94%
See 1 more Smart Citation
“…The results showed that the incidence of peripheral neuropathy was more experienced by women (Table 3). By some previous studies, it is stated that about 53% more who experience peripheral neuropathy are women (30,31).…”
Section: Overview Of Peripheral Neuropathy Based On Demographic Characteristicsmentioning
confidence: 94%
“…This study shows that the incidence of diabetic peripheral neuropathy is more experienced by middle and late adult age categories (Table 4). Corresponding to this states that the average person with diabetes who has neuropathy in middle adulthood is around 51 years (30). Strengthened by research in Manado states that the age range of 46-65 years is the most frequent category of diabetic peripheral neuropathy (33).…”
Section: Overview Of Peripheral Neuropathy Based On Demographic Characteristicsmentioning
confidence: 99%
“…Hasil ini senada dengan penelitian-penelitian sebelumnya melalui tahapan pemeriksaan fisik yang sama menunjukkan mayoritas responden memiliki derajat neuropati ringan. 17,18 Neuropati ringan dapat berkembang menjadi neuropati sedang hingga berat jika tidak dilakukan perawatan dengan tepat. Hasil penelitian menunjukan adanya perbedaan perilaku perawatan kaki diabetisi sebelum dan sesudah diberikan perawatan kaki 3F yang sebagian besar perawatan kaki dapat dilakukan oleh pasien secara mandiri.…”
Section: Pembahasanunclassified